Mediumistic Phenomena by Julian Ochorowicz - Weaver, Zofia (Journal of Scientific Exploration, 2018)
Translated by Casimir Bernard and Zofia Weaver and edited by Zofia Weaver. Mediumistic Phenomena by Julian Ochorowicz is the title of a series of booklets, in six parts, published in Polish from 1913-1915. This translation covers just the first two parts, describing the author’s first encounter with Eusapia Palladino in Italy in 1893, and her subsequent visit to Warsaw. Ochorowicz wrote these accounts immediately after the events they describe, but because of the hostility to the subject of mediumship in Poland they remained unpublished in his desk for 19 years. The next four parts, not translated here, cover other material, mostly experiments with Stanisława Tomczyk (who was to become Mrs Everard Feilding in 1919) and the controversy over the photographs relating to them. Julian Ochorowicz was a charismatic personality, active at the very centre of Warsaw’s intellectual and artistic life. Even after he moved away from Warsaw to the far south of Poland, he drew many distinguished visitors to his new abode, and his presence there helped to turn it into a very popular resort. However, his interests (and perhaps his uncompromising manner of promoting them) did not make him popular with the orthodox scientific community. By now his contribution in many branches of learning, particularly psychology, has been recognised in Poland, and his reputation restored. However, as in the case of many other prominent figures, his “belief in the reality of mediumistic phenomena” is presented as a misguided aberration, especially when “Hugo Münsterberg, in an extremely simple and clever way, proved her [Eusapia] to be fraudulent in moving a table with her foot in 1909” (Stachowski, 1996). While Münsterberg did nothing of the sort, Ochorowicz knew a great deal about cheating and was always on the lookout for it, as the following text makes clear. There is caution, there is objectivity, but there is also an exuberance and a vitality in these early encounters between Ochorowicz and Eusapia’s phenomena which I think make fascinating reading. More than half of this translation was the work of Casimir Bernard, a Polish researcher now deceased. He lived in the USA and did the translation because he thought it was worth doing, and sent it to me many years ago. Since then, the relevant parts of Mediumistic Phenomena have been reprinted in Poland, which meant that I could obtain the Polish text and translate the missing parts – because I also think it is worth doing. However, not everything seemed relevant, and for this reason parts of the text are omitted and parts are summarised. The omissions are indicated by [...], while the summaries are in italics and in square brackets. ---Zofia Weaver